The Effect of Paraffinic Mineral Oil Lubrication in Cold Forward Extrusion - Sulaiman, Mohd Hafis - (International Journal of Integrated Engineering, 2011)
This paper presents the results of cold forward extrusion modelling and the analysis of the contact sliding behaviour on the die-billet surface by paraffinic mineral oil lubrication with kinematic viscosity of 92 mm2/s at 40 °C. The analysis dealt with the plasticity flow that was investigated by finite element method in order to identify the loads acting on the billet. The finite element analysis of stresses was performed based on load distributions calculated from experimental test. The time behaviour of the displacements on the billet was then used as inputs for the extrusion model. The present method provided good results with reduced computation time. The results of the extrusion model revealed that the zones of high stress situated at the sharp edges of the die, which explains the observed extrusion force to reach a peak value.